Post-harvest characteristics of black Sigatoka resistant banana, cooking banana and plantain hybrids - Dadzie, B.K. (1998)
This manual is based on the results of 2.5 years (1993-1995) of research work conducted at the Fundación Hondureña de Investigación Agrícola (FHIA) in Honduras. The manual describes post-harvest characteristics at harvest, maturation, green-life, ripening quality and organoleptic features of black Sigatoka resistant hybrids. Chapter 1 is devoted to two banana hybrids (FHIA-01 and FHIA-02) with comparisons to two commercial cultivars (Grande Naine and Williams). Chapter 2 describes one cooking banana hybrid (FHIA-03). In chapter 3, two plantain hybrids (FHIA-21 and FHIA-22) are compared to Cuerno (Horn Plantain).